Nuclear medicine techniques a better weapon in detecting a rare case of epiphyseal osteomyelitis caused by Salmonella in a patient without sickle cell disease. Issue 9 (2013) - Caobelli, F; Magli, F; Pizzocaro, C
No abstract available